Butterfly Hug Therapy in Enhancing Self-Acceptance Among High School Female Students - Hidayat, Alifian Nur; Wahyuni , Ridha (Eduvest - Journal of Universal Studies, 2024)
This transitional period experiences significant changes that may be followed by various crises as it relates to identity formation, self-image, body image. Self-acceptance can help adolescents achieve a more positive self. Butterfly hug therapy is one way to increase self-acceptance. This study aims to determine the effect of butterfly hug therapy on self-acceptance in high school students. Quantitative methods with a pseudo-experimental design were used in this study. Involving 34 high school students, data were obtained using a self-acceptance scale. The data collected were then analyzed with the results of the study showing that: 1) independent sample t-test, obtained a sig value. (2-tailed) of 0.000 <0.05 which means there is a difference in the average self-acceptance results between the experimental class of butterfly hug therapy and the control class. Hypothesis testing shows that H1 is accepted and H0 is rejected with the research hypothesis that there is an effect of increasing self-acceptance in adolescent girls who are treated with butterfly hug therapy; 2) Spearman rank test on the experimental group showed a correlation coefficient of 0.922**. This means that the level of relationship strength (correlation) between the experimental class posttest results and the experimental class sustain effect is 0.922 or very strong. It can be concluded that the treatment given has a long-term effect with a range of 1 week after treatment.